Odpowiedzi

2010-02-08T22:07:56+01:00
Najlepsza Odpowiedź!
2010-02-08T22:16:32+01:00
A)-2a+b-a-2b+3a= (-b)
b)-ab+b do kw + 3ab-2ab = b do kw.
e)0,2x do kw.-2y =1,8x do kw + 4,3y - x= (-1,6do kw.) + 2,3y
f) -1/4m + 1/8 n -1/8m + 0,375m= 1/8n


nad tym ostatnim się bardzo długo zastanawiałam i myślę że jest dobrze !!

jak by co mam z tego 5 ;)
2010-02-08T22:16:41+01:00
A) -2a+b-a-2b+3a=-b
b)-ab+b do kw+3ab-2ab=b do kw
e)0,2xdo kw-2y=1,8xdo kw +4,3y-x=0,2x+1,8xdo kw =2,3y
f)-1/4m+1/8n-1/8m+375m=2/8m-1/8m+375m-1/8n=375 1/8m-1/8n